Respostas fisiológicas de Solanum Iycopersicum L. sob densidades crescentes de nematoides e ácido salicílíco - Figueiredo, Francisco Romário Andrade (2019)
Tomato (Solanum lycopersicum L.) is one of the most important oleraceous in the world, and it is subject to the attack of several pathogens, especially to the nematodes of the galls, that can promote physiological disorders that make the crop unviable. In view of this problem, it is necessary to search for strategies that minimize these effects, so the application of salicylic acid may be a promising strategy. In this context, the objective of this work was to evaluate the physiological responses of tomato plants under the population densities of Meloidogyne javanica and salicylic acid application. The design was the one of randomized blocks, using the Central Composite Box (CCB) with five nematode population densities (0, 5815, 20000, 34184 and 40000 eggs per pot) and five doses of salicylic acid (0.0, 0.29, 1.0, 1.71 and 2.0 mM), with four replicates and two plants per experimental plot. The following variables were evaluated: plant height, stem diameter, number of leaves, leaf area, specific leaf area, leaf specific weight, absolute and relative growth rate for height, root volume, aerial shoot mass, mass root dry matter, total dry mass, Dickson quality index, number of eggs, number of galls and reproduction factor at 50 days after transplanting and soil infestation. Gas exchanges, fluorescence and chlorophyll index were evaluated at 45 days after transplanting and soil infestation. The population density (PD) of 23903 eggs provided the largest reproduction factor, however, the PDs did not influence the growth characteristics of the tomato. Salicylic acid (SA) influenced the absolute growth rate for height, specific leaf area and leaf specific weight. SA influenced the net CO2 assimilation and carboxylation efficiency. The infestation by M. javanica in tomato plants had a negative influence on gas exchange and chlorophyll content.